Effects of microbial inoculant and additives on pile composting of cow manure - Yang, Qian; Zhang, Shiqiu; Li, Xueping; Rong, Kun; Li, Jialiang; Jiang, Lihua (Frontiers in Microbiology, 2023)
Composting is an effective method of recycling organic solid waste, and it is the key process linking planting with recycling. To explore the reuse of agricultural organic solid waste as a resource in the Yellow River Delta, the effects of microbial inoculant and different additives (calcium superphosphate, biochar, tomato straw, rice husk, and sugar residue) on aerobic pile composting of cow dung were studied to obtain the best composting conditions. The microbial inoculant and additives all played positive roles in the process of aerobic composting, and the experimental groups outperformed the control groups without any additives. In addition, the microbial inoculant promoted rapid pile body heating more than the recovery materials alone, and the effects on aerobic composting were related to the organic matter of substrates and biochar. Degradation of additives into humic acid might serve as electron shuttles to promote thorough organic matter decomposition. After being composted, all the materials were satisfactorily decomposed. These results provide a scientific basis data for industrial composting of organic solid waste processed by on-site stacking, and provide a reference for researcher and practitioners for studying the applications of microbial inoculant on aerobic composting.